Ferroptosis as a promising therapeutic strategy for melanoma - Na Ta; Xiaodong Jiang; Yongchun Zhang; Hongquan Wang (Frontiers Media S.A., 2023)
Malignant melanoma (MM) is the most common and deadliest type of skin cancer and is associated with high mortality rates across all races and ethnicities. Although present treatment options combined with surgery provide short-term clinical benefit in patients and early diagnosis of non-metastatic MM significantly increases the probability of survival, no efficacious treatments are available for MM. The etiology and pathogenesis of MM are complex. Acquired drug resistance is associated with a pool prognosis in patients with advanced-stage MM. Thus, these patients require new therapeutic strategies to improve their treatment response and prognosis. Multiple studies have revealed that ferroptosis, a non-apoptotic form of regulated cell death (RCD) characterized by iron dependant lipid peroxidation, can prevent the development of MM. Recent studies have indicated that targeting ferroptosis is a promising treatment strategy for MM. This review article summarizes the core mechanisms underlying the development of ferroptosis in MM cells and its potential role as a therapeutic target in MM. We emphasize the emerging types of small molecules inducing ferroptosis pathways by boosting the antitumor activity of BRAFi and immunotherapy and uncover their beneficial effects to treat MM. We also summarize the application of nanosensitizer-mediated unique dynamic therapeutic strategies and ferroptosis-based nanodrug targeting strategies as therapeutic options for MM. This review suggests that pharmacological induction of ferroptosis may be a potential therapeutic target for MM.